MXene composite nanocellulose liquid crystal intelligent color-changing material as well as preparation method and application thereof
Through the preparation of MXene composite nanocellulose liquid crystal material, combined with MXene two-dimensional nanosheets and nanocellulose liquid crystal, the problem of poor color adjustment flexibility of existing intelligent color change materials is solved, and the flexible response of colors under multiple stimuli is achieved. Application in multiple fields.
Patent Information
- Application Number
- CN202310794552.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
Existing intelligent color-changing materials have the disadvantages of being unadjustable initial color, low color saturation, slow color-changing response speed, low color-changing response sensitivity and narrow color change range, making it difficult to flexibly adjust colors under various external stimuli.
Using MXene composite nanocellulose liquid crystal material, by combining MXene two-dimensional nanosheets with nanocellulose liquid crystals, adjusting their mass ratio and processing methods, an intelligent color-changing material with a self-assembled structure can be prepared at temperature, electric field, and magnetic field. Adjust the color under various stimuli such as light and stress.
It realizes flexible adjustments of initial color, color saturation, color change response speed and color change range, providing application potential in the fields of 3D printing, intelligent sensing, biomedical and intelligent robots.
Smart Images

Figure CN119220242A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of smart nanomaterials, and in particular to a MXene composite nanocellulose liquid crystal smart color-changing material, a preparation method and an application thereof. Background Art
[0002] Nature is the best source of inspiration for material design and manufacturing. Many advanced artificial materials are synthesized and manufactured by copying or imitating components, structures and systems in nature. Structural color is a unique color that originates from the physical interaction between light and the periodic submicron structure of matter, with excellent color purity, brightness and resistance to photochemical degradation. There are many types of photonic crystal structures in nature that can produce structural colors. For example, bright structural colors can be observed on the surfaces of some animals and plants. Structural color is a common phenomenon in natural organisms and is widely present in many life activities, including biological communication, camouflage and reproduction. In particular, many organisms use complex regulatory mechanisms to change their colors in response to various external stimuli, which helps them camouflage themselves in dangerous environments to avoid natural enemies, or send out warning and courtship signals when needed. A typical example is that chameleons can quickly change their skin color by adjusting the lattice spacing of three-dimensional photonic crystals in their skin, thereby achieving visual camouflage. For example, some cephalopods and chameleons can instantly adapt their colors to the surrounding background, beetles change their colors according to the humidity of the environment, and zebrafish change their appearance according to the ambient light conditions. Inspired by these organisms, more and more research has begun to focus on the development of structural color materials with stimulus-responsive functions. Such materials can change their own colors when stimulated by external stimuli, and have great application potential in the fields of sensors, displays, anti-counterfeiting, smart devices, etc. However, the currently developed smart color-changing materials have disadvantages such as unadjustable initial color, low color saturation, slow color change response speed, low color change response sensitivity, and narrow color change range.
[0003] As a typical sustainable biomass material, cellulose has an annual output of more than 90 billion tons and is the most abundant polymer on earth. Among the numerous cellulose derivatives, nano-chiral liquid crystal materials represented by cellulose nanocrystals and hydroxypropyl cellulose can self-assemble under certain conditions to produce cholesteric phase (also known as chiral nematic phase) liquid crystal structures with structural colors. Due to its advantages such as environmental friendliness, low cost, wide sources, mild assembly conditions, and adjustable colors, cellulose chiral liquid crystals have also become ideal raw materials for preparing bionic smart color-changing materials. MXene two-dimensional nanomaterials represent a large two-dimensional early transition metal carbide or nitride family with large specific surface area, excellent strength, good conductivity and high photothermal conversion efficiency. Composite nanocellulose liquid crystals with MXene two-dimensional nanomaterials are expected to prepare smart color-changing materials with excellent color-changing properties. However, composite materials based on nanocellulose liquid crystals and MXene have not been reported yet. MXene composite nanocellulose liquid crystal smart color-changing materials are expected to be used in important fields such as 3D printing, food, biomedicine, anti-counterfeiting, displays, sensors, soft robots, wearable electronic products and organ chips. Summary of the invention
[0004] The purpose of the present invention is to provide a MXene composite nanocellulose liquid crystal intelligent color-changing material in view of the technical defects existing in the prior art.
[0005] Another object of the present invention is to provide a method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material. The present invention also provides an application of a MXene composite nanocellulose liquid crystal intelligent color-changing material in the fields of 3D printing, intelligent sensing, etc.
[0006] The technical solution adopted to achieve the purpose of the present invention is:
[0007] A MXene composite nanocellulose liquid crystal intelligent color-changing material comprises nanocellulose liquid crystal with a self-assembled structure and MXene two-dimensional nanosheets.
[0008] In the above technical solution, the mass ratio of MXene two-dimensional nanosheets to nanocellulose liquid crystals is 1:100000 to 1:10.
[0009] A method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material comprises the following steps:
[0010] Step 1: Self-assembly of nanocellulose liquid crystals in solvent
[0011] Prepare a nanocellulose liquid crystal basic unit with self-assembly ability, select a target solvent, mix the nanocellulose liquid crystal basic unit and the target solvent evenly, and obtain a nanocellulose liquid crystal with a self-assembly structure;
[0012] Step 2: Dispersion of MXene 2D nanosheets in solvent
[0013] Prepare MXene two-dimensional nanosheets with high conductivity and high photothermal conversion efficiency, select a target solvent, mix the MXene nanosheets and the target solvent evenly, and obtain a MXene two-dimensional nanosheet dispersion;
[0014] Step 3: Mixing of Nanocellulose Liquid Crystals and MXene 2D Nanosheet Dispersion
[0015] The nanocellulose liquid crystal prepared in step 1 is evenly mixed with the MXene two-dimensional nanosheet dispersion prepared in step 2 to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0016] In the above technical scheme, in step 1, the nanocellulose liquid crystal basic unit with self-assembly ability is prepared by the following steps: removing the amorphous region of natural cellulose by a physical method to retain the crystalline region, or subjecting natural cellulose to an etherification reaction with an etherification agent after alkali treatment to prepare the nanocellulose liquid crystal basic unit with self-assembly ability;
[0017] The physical method is selected from one or more of acid hydrolysis, enzyme hydrolysis, biosynthesis, oxidation or ionic liquid method;
[0018] The etherifying agent includes but is not limited to propylene oxide.
[0019] In the above technical scheme, the natural cellulose raw material for preparing the nanocellulose liquid crystal in step 1 is selected from one or more of cotton, wood pulp, bamboo pulp or plant cellulose separated from agricultural and forestry lignocellulose waste, preferably microcrystalline cellulose and α-cellulose;
[0020] The nanocellulose liquid crystal basic unit with self-assembly ability in step 1 is selected from hydroxypropyl cellulose or cellulose nanocrystal.
[0021] In the above technical scheme, the target solvent in step 1 and step 2 is selected from one or more of water, dimethyl sulfoxide, ethylene glycol, dimethylformamide, aniline, formamide, acetonitrile, toluene, trifluoroacetic acid, methanol, ethanol, acetic acid, isopropanol, ether, dichloromethane, chloroform, and cyclohexane;
[0022] In the step 1, the mass ratio of the nanocellulose liquid crystal basic unit to the target solvent is 1:100 to 100:1;
[0023] In step 2, the mass ratio of the MXene two-dimensional nanosheets to the target solvent is 1:10000 to 1:0.
[0024] In the above technical solution, the MXene two-dimensional nanosheet in step 2 is selected from Ti3C2T x 、Ti2CT x 、Ti4N3T x 、Ti3CNT x 、Mo2TiC2T x 、Nb2CT x 、V2CT x One or more of the .
[0025] In the above technical solution, the mass ratio of the nanocellulose liquid crystal to the MXene nanosheet dispersion in step 3 is 10:0 to 1:100000.
[0026] Another aspect of the present invention also includes the application of the MXene composite nanocellulose liquid crystal intelligent color-changing material in the fields of 3D printing, biomedicine, human-computer interaction and intelligent robots.
[0027] In the above technical solution, the MXene composite nanocellulose liquid crystal intelligent color-changing material has an intelligent sensing color-changing process as follows:
[0028] The MXene composite nanocellulose liquid crystal intelligent color-changing material was placed on a clean glass slide and allowed to stand for 15 minutes to allow it to fully self-assemble to produce beautiful structural colors. It was then placed in a high and low temperature box and a program heating step was set. As the temperature increased, the peak of the reflection spectrum of the MXene composite nanocellulose liquid crystal intelligent color-changing material gradually red-shifted, and the color of the MXene composite nanocellulose liquid crystal intelligent color-changing material changed significantly. Under the conditions of external electric field changes, magnetic field changes, light and stress, the MXene composite nanocellulose liquid crystal intelligent color-changing material also has a similar color-changing effect.
[0029] In the above technical solution, the temperature range in which the MXene composite nanocellulose liquid crystal intelligent color-changing material changes color is -100°C to 300°C;
[0030] The electric field range for the color change of the MXene composite nanocellulose liquid crystal intelligent color-changing material is 0.1V / m to 200kV / m;
[0031] The magnetic field range in which the color of the MXene composite nanocellulose liquid crystal intelligent color-changing material changes is 0.2mG to 20G;
[0032] The light source for the color change of the MXene composite nanocellulose liquid crystal intelligent color-changing material is full-spectrum white light or light with a wavelength range of 800 to 1200 nm, and the light intensity is 20 mW / cm 2 ~1W / cm 2 ;
[0033] The external stress range for the color change of the MXene composite nanocellulose liquid crystal intelligent color-changing material is 0.01Pa to 10MPa.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1) The initial color of the MXene composite nanocellulose liquid crystal intelligent color-changing material provided by the present invention can be arbitrarily adjusted within the visible spectrum wavelength range, and can also be transparent or black. Its initial color, color saturation, color change response speed, color change response sensitivity and color change range can be adjusted by changing the ratio of MXene two-dimensional nanosheets and nanocellulose liquid crystal components in the composite ink. The material is expected to be applied in the fields of 3D printing, intelligent sensing, biomedicine, human-computer interaction and intelligent robots;
[0036] 2) The present invention composites MXene two-dimensional nanosheets with nanocellulose liquid crystals. The MXene two-dimensional nanosheets can be used as broadband absorbers and black substrates to significantly improve the saturation of the nanocellulose liquid crystal structural color. At the same time, the two-dimensional nanosheet morphology, high photothermal conversion efficiency and high conductivity of MXene give the smart color-changing material flexible and adjustable initial color, color change response speed, color change response sensitivity and color change range. Based on the excellent properties of nanocellulose liquid crystals and MXene two-dimensional nanosheets, the MXene composite nanocellulose liquid crystal smart color-changing material has a color change response to various stimulus factors such as ambient temperature changes, electric field changes, magnetic field changes, light and external stress;
[0037] 3) The MXene composite nanocellulose liquid crystal intelligent color-changing material provided by the present invention has the advantages of flexible and adjustable shape, easy processing and convenient storage, and can achieve long-term storage and flexible use under certain conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a scanning electron microscope photo of the cross section of hydroxypropyl cellulose nano liquid crystal;
[0039] Figure 2 is the reflection spectrum of aqueous solution containing different mass fractions of hydroxypropyl cellulose nano-liquid crystal;
[0040] Figure 3 Schematic diagram of the preparation process of MXene two-dimensional nanosheets;
[0041] Figure 4 This is a transmission electron microscope photo of MXene two-dimensional nanosheets;
[0042] Figure 5X-ray diffraction patterns of MXene two-dimensional nanosheets and original MAX phase (Ti3AlC2);
[0043] Figure 6 The reflectance spectra of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of MXene;
[0044] Figure 7 Digital camera photos of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of MXene;
[0045] Figure 8 The reflectance spectra of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of nanocellulose liquid crystals;
[0046] Fig. 9 Digital camera photos of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of nanocellulose liquid crystals;
[0047] Fig.10 The reflection wavelength of MXene composite nanocellulose liquid crystal smart color-changing material at different temperatures;
[0048] Fig.11 Digital camera photos of MXene composite nanocellulose liquid crystal smart color-changing materials at different temperatures;
[0049] Fig.12 Digital camera photos of MXene composite nanocellulose liquid crystal smart color-changing materials under different compressive stresses;
[0050] Fig.13 The reflection wavelength of MXene composite nanocellulose liquid crystal smart color-changing material under different compressive stresses;
[0051] Fig.14 These are digital camera photos of the MXene composite nanocellulose liquid crystal smart color-changing material after being irradiated with 808nm infrared light for different time periods;
[0052] Fig.15 This is a photo of stretched color-changing fibers prepared using MXene composite nanocellulose liquid crystal smart color-changing materials;
[0053] Fig.16 MXene composite nanocellulose liquid crystal intelligent color-changing material with TJU letter pattern printed by 3D;
[0054] Fig.17 This is a photo of core-shell structured fibers prepared by coaxial extrusion 3D printing based on MXene composite nanocellulose liquid crystal smart color-changing materials.
[0055] Fig.18 This is a MXene composite nanocellulose liquid crystal intelligent color-changing material stored in a transparent barrel. On the right side of the picture is a schematic diagram of the chiral helical self-assembly structure of the nanocellulose liquid crystal, and on the left side is a schematic diagram of the molecular structure of the MXene two-dimensional nanosheet. DETAILED DESCRIPTION
[0056] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0057] Example 1
[0058] A MXene composite nanocellulose liquid crystal intelligent color-changing material is prepared by the following steps:
[0059] (1) Nanocellulose liquid crystals were prepared using hydroxypropyl cellulose derived from microcrystalline cellulose.
[0060] 6.20g of hydroxypropyl cellulose derived from microcrystalline cellulose and 2.06g of deionized water were added to a 150ml mixing tank, and then the mixing tank was covered and placed in a planetary centrifugal mixer, first mixed at 1600rpm for 2 minutes to wet the hydroxypropyl cellulose with deionized water, then left to stand for 2 minutes, and finally mixed evenly at 1800rpm for 2 minutes. The mixed hydroxypropyl cellulose aqueous solution was centrifuged at 10000rpm for 30 minutes to obtain hydroxypropyl cellulose nano liquid crystals. The obtained cellulose nano liquid crystals were stored in a dark environment at 4°C for later use. Figure 1 This is a scanning electron microscope photograph of the cross section of hydroxypropyl cellulose nano-liquid crystal. It can be seen from the figure that hydroxypropyl cellulose nano-liquid crystal has a layer-by-layer self-assembled microstructure. Figure 2 This is the reflection spectrum of hydroxypropyl cellulose nano-liquid crystals. It can be seen from the figure that as the mass fraction of hydroxypropyl cellulose in the aqueous solution gradually increases, the reflection wavelength of hydroxypropyl cellulose nano-liquid crystals gradually blue-shifts.
[0061] (2) Preparation of Ti3C2T x Type MXene two-dimensional nanosheet dispersion.
[0062] In a 100mL plastic beaker, add 30mL of commercially available 12mol / L hydrochloric acid, then add 10mL of deionized water, and stir magnetically at room temperature for 5 minutes to obtain 40mL of 9mol / L dilute hydrochloric acid. Add 3.2g LiF and stir for 10 minutes. While stirring, slowly add 2g Ti3AlC2. Then place it in a 50℃ environment and let it stand for 30 hours. The obtained black liquid is evenly distributed into six 50mL centrifuge tubes, deionized water is added, shaken, centrifuged repeatedly at 3500rpm for 10 times, and the supernatant is collected. The collected supernatant is centrifuged at 9500rpm for 5 minutes to collect the precipitate, and the precipitate is freeze-dried to obtain MXene nanosheets. Take 1mg of MXene nanosheets and disperse them in 1.74g of water. Use an ultrasonic cell crusher to ultrasonicate for 5 minutes at 15% power in an ice bath to obtain a uniform MXene two-dimensional nanosheet aqueous dispersion.
[0063] Figure 3 Schematic diagram of the preparation process of MXene two-dimensional nanosheets.
[0064] Figure 4 This is a transmission electron microscope photo of MXene two-dimensional nanosheets. It can be seen from the picture that the MXene nanosheets have a two-dimensional nanosheet morphology.
[0065] Figure 5 This is the X-ray diffraction pattern of MXene two-dimensional nanosheets and the original MAX phase (Ti3AlC2). It can be seen from the figure that after the Ti3AlC2 powder is etched, the (104) crystal plane peak at 38.78° is weakened, and the (002) crystal plane peak decreases from 9.70° to 7.03°. The characteristic peaks of the MAX phase are significantly reduced, indicating that the MXene two-dimensional nanosheets are successfully synthesized.
[0066] (3) Preparation of MXene composite nanocellulose liquid crystal intelligent color-changing material: 8.26 g of hydroxypropyl nanocellulose liquid crystal and 1.74 g of MXene two-dimensional nanosheet aqueous dispersion were added to a 150 ml mixing tank and mixed at 1500 rpm for 30 minutes using a planetary centrifugal mixer to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0067] Figure 6 The reflectance spectra of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of MXene. It can be seen from the figure that as the mass fraction of MXene in the composite material gradually increases, the reflection wavelength of the composite material gradually blue-shifts.
[0068] Figure 7Digital camera photos of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of MXene. As can be seen from the figure, as the mass fraction of MXene in the composite material gradually increases, the color of the composite material changes from red to light green, dark green, dark blue and purple-black.
[0069] Figure 8 The reflectance spectra of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of nanocellulose liquid crystals. It can be seen from the figure that with the gradual increase of the mass fraction of nanocellulose liquid crystals in the composite material, the reflection wavelength of the composite material gradually blue-shifts.
[0070] Fig. 9 Digital camera photos of MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of nanocellulose liquid crystals. As can be seen from the figure, as the mass fraction of nanocellulose liquid crystals in the composite material gradually increases, the color of the composite material changes from black to red, green, blue and purple.
[0071] Fig.10 The reflection wavelength of MXene composite nanocellulose liquid crystal smart color-changing material at different temperatures. It can be seen from the figure that when the mass fraction of nanocellulose liquid crystal remains unchanged, the reflection wavelength of the composite material gradually red-shifts with the increase of temperature; at the same temperature, with the increase of the mass fraction of nanocellulose liquid crystal, the reflection wavelength of the composite material gradually blue-shifts.
[0072] Fig.11 These are digital camera photos of MXene composite nanocellulose liquid crystal smart color-changing materials at different temperatures. It can be seen from the figures that MXene composite nanocellulose liquid crystal smart color-changing materials containing different mass fractions of nanocellulose liquid crystals all have the intelligent response characteristic that the color changes with temperature.
[0073] Fig.12 These are digital camera photos of the MXene composite nanocellulose liquid crystal smart color-changing material under different compressive stresses. It can be seen from the figure that as the compressive stress gradually increases, the color of the MXene composite nanocellulose liquid crystal smart color-changing material gradually changes from red to blue.
[0074] Fig.13 This is the reflection wavelength of the MXene composite nanocellulose liquid crystal smart color-changing material under different compressive stresses. It can be seen from the figure that as the compressive stress gradually increases, the reflection wavelength of the MXene composite nanocellulose liquid crystal smart color-changing material gradually shifts to the blue.
[0075] Fig.14These are digital camera photos of the MXene composite nanocellulose liquid crystal smart color-changing material after being irradiated with 808nm infrared light for different times. It can be seen from the figure that as the irradiation time increases, the color of the MXene composite nanocellulose liquid crystal smart color-changing material gradually changes from blue to red.
[0076] Example 2
[0077] A MXene composite nanocellulose liquid crystal intelligent color-changing material is prepared by the following steps:
[0078] (1) Preparation of nanocellulose liquid crystals using hydroxypropyl cellulose derived from α-cellulose. 5.90 g of hydroxypropyl cellulose derived from α-cellulose and 1.97 g of dimethyl sulfoxide were added to a 150 ml mixing tank, and then the mixing tank was covered and placed in a planetary centrifugal mixer. The mixture was first mixed at 1300 rpm for 5 minutes to allow dimethyl sulfoxide to wet the hydroxypropyl cellulose, then allowed to stand for 3 minutes, and finally mixed evenly at 1600 rpm for 5 minutes. The mixed hydroxypropyl cellulose dimethyl sulfoxide solution was centrifuged at 8000 rpm for 40 minutes to obtain hydroxypropyl nanocellulose liquid crystals.
[0079] (2) Preparation of Ti2CT x Type MXene two-dimensional nanosheet dispersion. In a 100mL plastic beaker, add 30mL of commercially available 12mol / L hydrochloric acid, then add 10mL of deionized water, and stir magnetically at room temperature for 5 minutes to obtain 40mL of 9mol / L dilute hydrochloric acid. Add 3.2g LiF and stir for 10 minutes. While stirring, slowly add 9g Ti3AlC2. Then place it in a 50℃ environment and let it stand for 30 hours. The obtained black liquid is evenly distributed into six 50mL centrifuge tubes, deionized water is added, shaken, centrifuged repeatedly at 3500rpm for 10 times, and the supernatant is collected. The collected supernatant is centrifuged at 9500rpm for 5 minutes to collect the precipitate, and the precipitate is freeze-dried to obtain MXene nanosheets. Take 10mg MXene nanosheets and disperse them in 2.14g dimethyl sulfoxide. Use an ultrasonic cell crusher to ultrasonicate for 10 minutes at 5% power in an ice bath to obtain a uniform MXene two-dimensional nanosheet dimethyl sulfoxide dispersion.
[0080] (3) Preparation of MXene composite nanocellulose liquid crystal intelligent color-changing material: 7.86 g of hydroxypropyl nanocellulose liquid crystal and 2.14 g of MXene two-dimensional nanosheet dimethyl sulfoxide dispersion were added to a 150 ml mixing tank and mixed at 1800 rpm for 60 minutes using a planetary centrifugal mixer to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0081] (4) The prepared MXene composite nanocellulose liquid crystal intelligent color-changing material is injected into a commercially available polydimethylsiloxane hollow hose with a wall thickness of 1 mm using a syringe to obtain a stretched color-changing fiber. Fig.15 This is a photo of stretched color-changing fibers prepared using MXene composite nanocellulose liquid crystal smart color-changing materials.
[0082] Example 3
[0083] A MXene composite nanocellulose liquid crystal intelligent color-changing material and a preparation method and application thereof, comprising the following steps:
[0084] (1) Preparation of nanocellulose liquid crystals using hydroxypropyl cellulose derived from wood pulp. 6.50 g of hydroxypropyl cellulose derived from wood pulp and 2.17 g of N,N-dimethylformamide were added to a 150 ml mixing tank, and then the mixing tank was covered and placed in a planetary centrifugal mixer. The mixture was first mixed at 1700 rpm for 20 minutes to allow N,N-dimethylformamide to wet the hydroxypropyl cellulose, then allowed to stand for 10 minutes, and finally uniformly mixed at 1500 rpm for 30 minutes. The mixed hydroxypropyl cellulose N,N-dimethylformamide solution was centrifuged at 7500 rpm for 50 minutes to obtain hydroxypropyl nanocellulose liquid crystals.
[0085] (2) Preparation of Ti4N3T x Type MXene two-dimensional nanosheet dispersion. In a 100mL plastic beaker, add 30mL of commercially available 12mol / L hydrochloric acid, then add 10mL of deionized water, and stir magnetically at room temperature for 5 minutes to obtain 40mL of 9mol / L dilute hydrochloric acid. Add 3.2g LiF and stir for 10 minutes. While stirring, slowly add 6g TiAlN. Then place it in a 50℃ environment and let it stand for 30 hours. The obtained black liquid is evenly distributed into six 50mL centrifuge tubes, deionized water is added, shaken, centrifuged repeatedly at 3500rpm for 10 times, and the supernatant is collected. The collected supernatant is centrifuged at 9500rpm for 5 minutes to collect the precipitate, and the precipitate is freeze-dried to obtain MXene nanosheets. Take 100mg MXene nanosheets and disperse them in 1.33g N,N-dimethylformamide. Use an ultrasonic cell crusher to ultrasonicate at 8% power for 30 minutes in an ice bath to obtain a uniform MXene two-dimensional nanosheet N,N-dimethylformamide dispersion.
[0086] (3) Preparation of MXene composite nanocellulose liquid crystal intelligent color-changing material. 8.67 g of hydroxypropyl nanocellulose liquid crystal and 1.33 g of MXene two-dimensional nanosheet N,N-dimethylformamide dispersion were added to a 150 ml mixing tank and mixed at 1750 rpm for 120 minutes using a planetary centrifugal mixer to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0087] (4) Add the prepared MXene composite nanocellulose liquid crystal intelligent color-changing material into the barrel of a 3D printer and print it into a specific geometric shape using a 3D printer to obtain a 3D-printed MXene composite nanocellulose liquid crystal intelligent color-changing material component. Fig.16 This is a 3D printed MXene composite nanocellulose liquid crystal intelligent color-changing material with a TJU letter pattern. Through coaxial extrusion 3D printing technology, a core-shell structure fiber with an outer layer of polydimethylsiloxane and an inner layer of MXene composite nanocellulose liquid crystal intelligent color-changing material can be prepared. Fig.17 This is a photo of core-shell structured fibers prepared by coaxial extrusion 3D printing based on MXene composite nanocellulose liquid crystal smart color-changing materials.
[0088] Example 4
[0089] A MXene composite nanocellulose liquid crystal intelligent color-changing material is prepared by the following steps:
[0090] (1) Preparation of nanocellulose liquid crystal using cotton. First, crush the commercially available cotton wool into pieces of less than 1*1cm, and then weigh 20g of cotton wool on a balance for later use. Dilute the commercially available concentrated sulfuric acid with a mass fraction of 98wt% to 64wt% with deionized water for later use. Add 20g of cotton wool to 200mL of 64wt% sulfuric acid and soak it completely, and continue to react for 90 minutes in a 45℃ water bath with mechanical stirring at a speed of 600 rpm. After the reaction is completed, immediately dilute the reaction system with 1800mL of deionized water. After stirring evenly, let it stand for 12h. Then remove the supernatant, centrifuge the remaining milky white suspension at a speed of 5000 rpm for 5 minutes, pour out the supernatant after centrifugation, add deionized water to the precipitate, shake well and repeat the above centrifugation steps until the white suspension no longer separates after the centrifugation. At this time, collect the white suspension and discard the small amount of precipitate in the lower layer. Take a dialysis bag with a molecular weight cutoff of 8000-14000 and boil it with boiling deionized water for 10 minutes, then wash it with deionized water at room temperature. Pour the collected white suspension into the dialysis bag and dialyze it in deionized water. Change the water 3 times a day until the pH value of the deionized water on the outer layer of the dialysis bag reaches about 6. Use a rotary evaporator to concentrate the white suspension to a mass fraction of cellulose nanocrystals of 4wt% for later use.
[0091] (2) Preparation of Ti3CNT xType MXene two-dimensional nanosheet dispersion. In a 100mL plastic beaker, add 30mL of commercially available 12mol / L hydrochloric acid, then add 10mL of deionized water, and stir magnetically at room temperature for 5 minutes to obtain 40mL of 9mol / L dilute hydrochloric acid. Add 3.2g LiF and stir for 10 minutes. While stirring, slowly add 3g TiAlCN. Then place it in a 50℃ environment and let it stand for 30 hours. The obtained black liquid is evenly distributed into six 50mL centrifuge tubes, deionized water is added, shaken, and centrifuged repeatedly at 3500rpm for 10 times. The supernatant is collected, and the collected supernatant is centrifuged at 9500rpm for 5 minutes to collect the precipitate. The precipitate is freeze-dried to obtain MXene nanosheets. Take 100mg MXene nanosheets and disperse them in 1.33g deionized water. Use an ultrasonic cell crusher to ultrasonicate at 10% power for 30 minutes in an ice bath to obtain a uniform MXene two-dimensional nanosheet aqueous dispersion.
[0092] (3) Preparation of MXene composite nanocellulose liquid crystal intelligent color-changing material: 5.33 g of cellulose nanocrystal aqueous dispersion and 4.67 g of MXene two-dimensional nanosheet aqueous dispersion were added to a 150 ml mixing tank and mixed at 800 rpm for 12 minutes using a planetary centrifugal mixer to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0093] (4) The prepared MXene composite nanocellulose liquid crystal smart color-changing material was placed in an electric field of 50 V / m, 100 V / m and 150 V / m for 30 seconds respectively. It was found that with the increase of the electric field intensity, the color of the MXene composite nanocellulose liquid crystal smart color-changing material gradually changed from blue to red.
[0094] (5) The prepared MXene composite nanocellulose liquid crystal smart color-changing material was placed in a magnetic field of 10mG, 100mG and 1000mG respectively for 100s. It was found that with the increase of magnetic field intensity, the color of the MXene composite nanocellulose liquid crystal smart color-changing material gradually changed from blue to red.
[0095] Example 5
[0096] A MXene composite nanocellulose liquid crystal intelligent color-changing material is prepared by the following steps:
[0097] (1) Preparation of nanocellulose liquid crystal using hydroxypropyl cellulose derived from bamboo pulp. 35 g of hydroxypropyl cellulose derived from bamboo pulp and 15 g of ethylene glycol were added to a 150 ml mixing tank, and then the mixing tank was covered and placed in a planetary centrifugal mixer, first mixed at 1700 rpm for 20 minutes to allow the ethylene glycol to wet the hydroxypropyl cellulose, then left to stand for 10 minutes, and finally uniformly mixed at 1500 rpm for 30 minutes. The mixed hydroxypropyl cellulose ethylene glycol solution was centrifuged at 7500 rpm for 50 minutes to obtain hydroxypropyl nanocellulose liquid crystal.
[0098] (2) Preparation of Mo2TiC2Tx type MXene nanosheet dispersion. In a 100mL plastic beaker, add 30mL of commercially available 12mol / L hydrochloric acid, then add 10mL of deionized water, and stir magnetically at room temperature for 5 minutes to obtain 40mL of 9mol / L dilute hydrochloric acid. Add 3.2g of LiF and stir for 10 minutes. While stirring, slowly add 4g of Mo2TiC2Tx. Then place it in a 60℃ environment and let it stand for 25 hours. The obtained black liquid is evenly distributed into six 50mL centrifuge tubes, deionized water is added, shaken, and centrifuged repeatedly at 3500rpm for 10 times, and the supernatant is collected. The collected supernatant is centrifuged at 9500rpm for 5 minutes to collect the precipitate, and the precipitate is freeze-dried to obtain MXene nanosheets. Take 100mg of MXene nanosheets and disperse them in 1.33g of ethylene glycol. Use an ultrasonic cell crusher to ultrasonicate at 6% power for 30 minutes in an ice bath to obtain a uniform MXene two-dimensional nanosheet ethylene glycol dispersion.
[0099] (3) Preparation of MXene composite nanocellulose liquid crystal intelligent color-changing material: 3.23 g of hydroxypropyl nanocellulose liquid crystal and 6.77 g of MXene two-dimensional nanosheet ethylene glycol dispersion were added to a 150 ml mixing tank and mixed at 750 rpm for 20 minutes using a planetary centrifugal mixer to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0100] Example 6
[0101] A MXene composite nanocellulose liquid crystal intelligent color-changing material is prepared by the following steps:
[0102] (1) Preparation of nanocellulose liquid crystals using hydroxypropyl cellulose derived from agricultural and forestry lignocellulose. 6 g of hydroxypropyl cellulose derived from agricultural and forestry lignocellulose and 89 g of aniline were added to a 150 ml mixing tank, and then the mixing tank was covered and placed in a planetary centrifugal mixer. The mixture was first mixed at 1700 rpm for 20 minutes to allow the aniline to wet the hydroxypropyl cellulose, then allowed to stand for 10 minutes, and finally uniformly mixed at 1500 rpm for 30 minutes. The mixed hydroxypropyl cellulose aniline solution was centrifuged at 7500 rpm for 50 minutes to obtain hydroxypropyl nanocellulose liquid crystals.
[0103] (2) Preparation of Nb2CTx type MXene two-dimensional nanosheet dispersion. In a 100mL plastic beaker, add 30mL of commercially available 12mol / L hydrochloric acid, then add 10mL of deionized water, and stir magnetically at room temperature for 5 minutes to obtain 40mL of 9mol / L dilute hydrochloric acid. Add 3.2g of LiF and stir for 10 minutes. While stirring, slowly add 3g of Nb2AlC. Then place it in a 50℃ environment and let it stand for 30 hours. The obtained black liquid is evenly distributed into six 50mL centrifuge tubes, deionized water is added, shaken, and centrifuged repeatedly at 3500rpm for 10 times, and the supernatant is collected. The collected supernatant is centrifuged at 9500rpm for 5 minutes to collect the precipitate, and the precipitate is freeze-dried to obtain MXene nanosheets. Take 100mg of MXene nanosheets and disperse them in 1.33g of aniline. Use an ultrasonic cell crusher to ultrasonicate at 5% power for 20 minutes in an ice bath to obtain a uniform MXene two-dimensional nanosheet aniline dispersion.
[0104] (3) Preparation of MXene composite nanocellulose liquid crystal intelligent color-changing material: 7.29 g of hydroxypropyl nanocellulose liquid crystal and 2.71 g of MXene nanosheet aniline dispersion were added to a 150 ml mixing tank and mixed at 1650 rpm for 100 minutes using a planetary centrifugal mixer to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0105] Example 7
[0106] A MXene composite nanocellulose liquid crystal intelligent color-changing material is prepared by the following steps:
[0107] (1) Preparation of nanocellulose liquid crystals using hydroxypropyl cellulose derived from cotton. 102 g of hydroxypropyl cellulose derived from cotton and 20 g of ethanol were added to a 150 ml mixing tank, and then the mixing tank was covered and placed in a planetary centrifugal mixer. The mixture was first mixed at 1700 rpm for 20 minutes to allow the ethanol to wet the hydroxypropyl cellulose, then allowed to stand for 10 minutes, and finally uniformly mixed at 1500 rpm for 30 minutes. The mixed hydroxypropyl cellulose ethanol solution was centrifuged at 7500 rpm for 50 minutes to obtain hydroxypropyl nanocellulose liquid crystals.
[0108] (2) Preparation of V2CTx type two-dimensional MXene nanosheet dispersion. In a 100mL plastic beaker, add 30mL of commercially available 12mol / L hydrochloric acid, then add 10mL of deionized water, and stir magnetically at room temperature for 5 minutes to obtain 40mL of 9mol / L dilute hydrochloric acid. Add 3.2g LiF and stir for 10 minutes. While stirring, slowly add 5g V4AlC3. Then place it in a 50℃ environment and let it stand for 30 hours. The obtained black liquid is evenly distributed into six 50mL centrifuge tubes, deionized water is added, shaken, and centrifuged repeatedly at 3500rpm for 10 times, and the supernatant is collected. The collected supernatant is centrifuged at 9500rpm for 5 minutes to collect the precipitate, and the precipitate is freeze-dried to obtain MXene nanosheets. Take 100mg MXene nanosheets and disperse them in 1.33g ethanol. Use an ultrasonic cell crusher to ultrasonicate at 8% power for 5 minutes in an ice bath to obtain a uniform MXene two-dimensional nanosheet ethanol dispersion.
[0109] (3) Preparation of MXene composite nanocellulose liquid crystal intelligent color-changing material: 6.93 g of hydroxypropyl nanocellulose liquid crystal and 3.07 g of MXene two-dimensional nanosheet ethanol dispersion were added to a 150 ml mixing tank and mixed at 1350 rpm for 30 minutes using a planetary centrifugal mixer to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A MXene composite nanocellulose liquid crystal intelligent color-changing material, characterized in that: Including nanocellulose liquid crystals and MXene two-dimensional nanosheets with self-assembled structures.
2. A MXene composite nanocellulose liquid crystal intelligent color-changing material according to claim 1, characterized in that: The mass ratio of MXene two-dimensional nanosheets to nanocellulose liquid crystals is 1:100000 to 1:
10.
3. A method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material, characterized in that: The following steps are involved: Step 1: Self-assembly of nanocellulose liquid crystals in solvent Prepare a nanocellulose liquid crystal basic unit with self-assembly ability, select a target solvent, mix the nanocellulose liquid crystal basic unit and the target solvent evenly, and obtain a nanocellulose liquid crystal with a self-assembly structure; Step 2: Dispersion of MXene 2D nanosheets in solvent Prepare MXene two-dimensional nanosheets with high conductivity and high photothermal conversion efficiency, select a target solvent, mix the MXene nanosheets and the target solvent evenly, and obtain a MXene two-dimensional nanosheet dispersion; Step 3: Mixing of Nanocellulose Liquid Crystals and MXene 2D Nanosheet Dispersion The nanocellulose liquid crystal prepared in step 1 is evenly mixed with the MXene two-dimensional nanosheet dispersion prepared in step 2 to obtain a MXene composite nanocellulose liquid crystal intelligent color-changing material.
4. The method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material according to claim 3, characterized in that: In step 1, the nanocellulose liquid crystal basic unit with self-assembly ability is prepared by the following steps: The amorphous region of natural cellulose is removed by physical methods to retain the crystalline region, or the natural cellulose is subjected to an etherification reaction with an etherification agent after alkali treatment to prepare a nanocellulose liquid crystal basic unit with self-assembly ability; The physical method is selected from one or more of acid hydrolysis, enzyme hydrolysis, biosynthesis, oxidation or ionic liquid method; The etherifying agent includes but is not limited to propylene oxide.
5. The method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material according to claim 3, characterized in that: The natural cellulose raw material for preparing the nanocellulose liquid crystal in step 1 is selected from one or more of cotton, wood pulp, bamboo pulp or plant cellulose separated from agricultural and forestry lignocellulose waste, preferably microcrystalline cellulose and α-cellulose; The nanocellulose liquid crystal basic unit with self-assembly ability in step 1 is selected from hydroxypropyl cellulose or cellulose nanocrystal.
6. The method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material according to claim 3, characterized in that: In step 1 and step 2, the target solvent is selected from one or more of water, dimethyl sulfoxide, ethylene glycol, dimethylformamide, aniline, formamide, acetonitrile, toluene, trifluoroacetic acid, methanol, ethanol, acetic acid, isopropanol, ether, dichloromethane, chloroform, and cyclohexane; In the step 1, the mass ratio of the nanocellulose liquid crystal basic unit to the target solvent is 1:100 to 100:1; In step 2, the mass ratio of the MXene two-dimensional nanosheets to the target solvent is 1:10000 to 1:
0.
7. The method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material according to claim 3, characterized in that: In step 2, the MXene two-dimensional nanosheet is selected from Ti3C2T x 、Ti2CT x 、Ti4N3T x 、Ti3CNT x 、Mo2TiC2T x 、Nb2CT x 、V2CT x One or more of the .
8. The method for preparing a MXene composite nanocellulose liquid crystal intelligent color-changing material according to claim 3, characterized in that: The mass ratio of the nanocellulose liquid crystal to the MXene nanosheet dispersion in step 3 is 10:0 to 1:100000.
9. The use of the MXene composite nanocellulose liquid crystal intelligent color-changing material according to claim 1, characterized in that: The MXene composite nanocellulose liquid crystal intelligent color-changing material is used in the fields of 3D printing, biomedicine, human-computer interaction or intelligent robots.
10. The use according to claim 9, characterized in that The temperature range in which the MXene composite nanocellulose liquid crystal intelligent color-changing material changes color is -100°C to 300°C; The electric field range for the color change of the MXene composite nanocellulose liquid crystal intelligent color-changing material is 0.1V / m to 200kV / m; The magnetic field range in which the color of the MXene composite nanocellulose liquid crystal intelligent color-changing material changes is 0.2mG to 20G; The light source for the color change of the MXene composite nanocellulose liquid crystal intelligent color-changing material is full-spectrum white light or light with a wavelength range of 800 to 1200 nm, and the light intensity is 20 mW / cm 2 ~1W / cm 2 ; The external stress range for the color change of the MXene composite nanocellulose liquid crystal intelligent color-changing material is 0.01Pa to 10MPa.
Citation Information
Cited By
Preparation method and application of high-sensitivity temperature-responsive cellulose-based structural color material
CN121293566A
Food colorant-enhanced HPC photonic gels, food colorant-enhanced HPC photonic gel films, and preparation thereof
CN121699255A
